Finding of roots of the matrix transcendental characteristic equation using Lambert W function - Ivanovienė, Irma; Rimas, Jonas (Lietuvos matematikos rinkinys, 2011)
The method of finding roots of the matrix transcendental characteristic equation, corresponding to linear matrix differential equation with delayed argument, is analyzed. The examples of the application of the method are presented.